(untitled) (Revista de História da UEG (REVHIST), 2023)
The focus of this article is investigate the process of dispersion and adaptation of African fish in Brazil in the years 1950-1990, especially of the tilapia species (niloticus, Rendalli), based on the discourse analysis of the Brazilian magazine Globo Rural and technical-agricultural documents. In recent history, based on processes of modernization and globalization of agriculture, the grafting of exotic species has contributed to a context of Great Acceleration (McNeill, Engelke, 2014) in the transformation of environments, especially in tropical regions as in the case of the Brazil where impacts on agrobiodiversity are also expressive. Tilapia has a history of more than four thousand years where it was introduced in many regions of the world, however it was during the second half of the twentieth century that its dispersion accentuated, because it became part of the chain of aquaculture related to agribusiness and, in Brazil it was considered a “jewel and a plague” according to the national press. It is noticed that, by guiding and propagating among the farmers, an alleged need to raise tilapias in a confined and controlled space, "a herd in the waters", the Globo Rural magazine not only documented the dispersion of tilapias in the country, but also acted as a “conductor of conduct” (FOUCAULT, 2014). Keywords: Tilapia. Aquaculture. Globo Rural. Environmental History. Biological Dispersion.